2017
DOI: 10.1016/j.neuron.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Integration of Artificial Sensory Feedback during Operant Conditioning of Motor Cortex Neurons

Abstract: SummaryNeuronal motor commands, whether generating real or neuroprosthetic movements, are shaped by ongoing sensory feedback from the displacement being produced. Here we asked if cortical stimulation could provide artificial feedback during operant conditioning of cortical neurons. Simultaneous two-photon imaging and real-time optogenetic stimulation were used to train mice to activate a single neuron in motor cortex (M1), while continuous feedback of its activity level was provided by proportionally stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 50 publications
14
90
0
Order By: Relevance
“…Previous work indicates that subjects can learn to control neuroprosthetic devices using single cells or bulk electrophysiological signals (Fetz, 1969;Bakay and Kennedy, 1998;Nicolelis, 2001;Serruya et al, 2002;Carmena et al, 2003;Weiskopf et al, 2003;Sitaram et al, 2007;Koralek et al, 2012;Hochberg et al, 2012;Collinger et al, 2013;Clancy et al, 2014;Sadtler et al, 2014;Prsa et al, 2017;Sitaram et al, 2017;Trautmann et al, 2019), but this is the first work, to our knowledge, to employ control using imaged population calcium signals. This technique allowed us to monitor much of the dorsal cortical network as animals learned neuroprosthetic control, whereas previous BMI work has been limited to recording from neighbouring neurons (Koralek et al, 2012;Clancy et al, 2014;Sadtler et al, 2014;Prsa et al, 2017). Using population signals, rather than individual neurons, to manipulate neuroprosthetic devices might afford more stable and minimally invasive control, robust to losing signals from single control cells.…”
Section: Discussionmentioning
confidence: 93%
“…Previous work indicates that subjects can learn to control neuroprosthetic devices using single cells or bulk electrophysiological signals (Fetz, 1969;Bakay and Kennedy, 1998;Nicolelis, 2001;Serruya et al, 2002;Carmena et al, 2003;Weiskopf et al, 2003;Sitaram et al, 2007;Koralek et al, 2012;Hochberg et al, 2012;Collinger et al, 2013;Clancy et al, 2014;Sadtler et al, 2014;Prsa et al, 2017;Sitaram et al, 2017;Trautmann et al, 2019), but this is the first work, to our knowledge, to employ control using imaged population calcium signals. This technique allowed us to monitor much of the dorsal cortical network as animals learned neuroprosthetic control, whereas previous BMI work has been limited to recording from neighbouring neurons (Koralek et al, 2012;Clancy et al, 2014;Sadtler et al, 2014;Prsa et al, 2017). Using population signals, rather than individual neurons, to manipulate neuroprosthetic devices might afford more stable and minimally invasive control, robust to losing signals from single control cells.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study by Prsa and colleagues showed that feedback via optogenetic neural stimulation is sufficient to drive BMI learning [25]**. This demonstrates a BMI where sensory feedback is delivered to specific, experimenter-defined nodes within the brain, paired with experimenter- defined command nodes (Fig.…”
Section: Manipulations To Probe Bmi Learningmentioning
confidence: 96%
“…Activity of corticomotor-neuronal cells can be divorced from muscle activity with feedback training [21] and subjects can learn decoders with arbitrary relationships between neural activity and movement [15]. BMI learning is also associated with differential modulation of command nodes relative to nearby nodes [14,18,2225] and cortico-striatal interactions specific to command nodes [26]. While the precise neural mechanisms of neurofeedback learning are not fully understood (e.g.…”
Section: Parsing Bmi Learningmentioning
confidence: 99%
See 2 more Smart Citations